ANALISIS PENERAPAN PROTOKOL CHSE DI HOTEL BERBINTANG DI KABUPATEN TABANAN - Nelsye Lumanauw; Luh Sri Damayanti; Dinar Sukma Pramesti (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2023)
This research aimed at analyzing the implementation of CHSE protocol and the strategies applied by the managements of star hotels in Tabanan Regency in welcoming the new normal era. This was descriptive qualitative research involving two hotels that were Natya Hotel and Nirjhara. Data were collected by doing observation, interview, and document analysis. The data were analyzed qualitatively. The results showed that the hotels implemented the CHSE protocol well as it was mentioned by the Ministry of Creative Economic and Tourism of Republic of Indonesia. To welcome the new normal era, the hotels applied several strategies. The first strategy was publishing the information about CHSE protocol implemented in the hotels to the public to build trust and providing discounts and promotion to attract guests to stay. Besides hotels also developed official procedures of CHSE implementation to maintain the consistency of the implementation of the protocol.